Free versus pedicled flaps for hand reconstruction: A systematic review and meta-analysis - Haya Abdulaziz Alzahrani; Mohammed Nasser Asiri; Abdulsalam M. Humedi; Juman Alammar; Hajar Alrashed; Faisal Hakami (JPRAS Open, 2025)
Background: Hand reconstruction is a critical component of plastic surgery, addressing congenital, traumatic, and degenerative conditions. Free and pedicled flaps are commonly used for hand defect repair. Aim: This systematic review was to compare the outcomes of free versus pedicled flaps in hand reconstruction. Methods: a search was conducted in October 2024 across PubMed, Web of Science, and Ovid MEDLINE using keywords such as “free tissue flaps,” “pedicled flaps,” and “hand reconstruction.” Eligible studies included randomized controlled trials, cohort studies, and clinical trials. Data on flap survival, complications, and patient satisfaction were extracted independently. Results: Nine studies involving 839 hands were included. Free flaps had a lower revision surgery rate (24 % vs. 61 %), while pedicled flaps showed fewer infections (8 % vs. 13 %) and less flap necrosis (8 % vs. 9 %). Conclusion: Free flaps offer lower revision rates, while pedicled flaps present fewer complications. This systematic review represents level III evidence.